EKSPLORASI NILAI SOSIAL TRADISI MADDOJA BINE SEBAGAI SUMBER BELAJAR IPS KELAS VII DI SMP NEGERI 1 MARIORIWAWO KABUPATEN SOPPENG SULAWESI SELATAN - Nuraevi; Shasliani; Ibrahim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social studies learning at SMP Negeri 1 Marioriwawo is still textbook-centered, thus not providing a contextual and meaningful learning experience. The Maddoja Bine tradition has the potential to be a social studies learning resource that enriches the material while instilling social values, character, and cultural identity in students. This study aims to describe the Maddoja Bine tradition in Soppeng Regency, identify the social values ​​contained therein, and analyze teachers' efforts in integrating these social values ​​as a social studies learning resource for grade VII at SMP Negeri 1 Marioriwawo. This study uses a qualitative approach with a descriptive exploratory research type. Data collection techniques are carried out through observation, interviews, and documentation. The results show that the Maddoja Bine tradition in Soppeng Regency is an agricultural practice of the Bugis community that is carried out by staying awake all night as a form of respect for Sangiang Serri (the goddess of rice). This tradition contains the values ​​of mutual cooperation (sibali reso), mutual respect (sipakatau), and unity (masseddi). The teacher's efforts to integrate it as a learning resource for class VII IPS at SMP Negeri 1 Marioriwawo were carried out through the development of teaching materials, the use of contextual approaches, and role models.